Association between remnant cholesterol and depression in middle-aged and older Chinese adults: a population-based cohort study - Zhou, Yang; Lin, Yan; Yang, Yanhui; Lei, Wang; Xu, Juan; Zhu, Yuanzeng (Frontiers in Endocrinology, 2025)
BackgroundThe focus on remnant cholesterol (RC) has intensified because of its association with various diseases. In this study, we investigated the association between RC and depression in middle-aged and older adults.MethodsThe study involved 7,305 participants from the 2015 and 2018 waves of the China Health and Retirement Longitudinal Study. Based on the 10-item Center for Epidemiological Studies Depression Scale (CESD-10), depression was indicated by scores ≥ 12. To assess the correlation between RC levels and depression, a logistic regression model that incorporated restricted cubic spline techniques was used.ResultsOf the study population, (mean age: 60.0 ± 9.5 years), 50.3% were female. From 2015 to 2018, the mean CESD-10 score increased from 6.31 ± 3.56 to 7.85 ± 5.23. Following adjustment for confounding factors, individuals in the higher RC level quartile exhibited a higher depression risk (Q3: odds ratio [OR]: 1.75, 95% confidence intervals [CI]: 1.29–2.39; Q4: OR: 2.68, 95% CI: 1.96–3.68, P for trend < 0.001), with a linear correlation between RC levels and depression (P for nonlinearity = 0.108). And the subgroup analysis yielded results consistent with the primary findings.ConclusionThis study revealed that in China, in middle-aged and older individuals, elevated RC levels were associated with a higher depression risk, suggesting RC is a promising target for depression prevention and treatment.